Balinese Local Wisdom Illustrated Story E-Book "Family Medicinal Plants" to Improve Science Literacy of Fourth Grade Elementary School Students - Ni Wayan Serra Yuni Ari Cahyani; I Gede Margunayasa; I Wayan Kertih (Journal of Education Reseach and Evaluation, 2026)
The current problem is the low scientific literacy of elementary school students, which is influenced by suboptimal use of digital media and the underutilization of local wisdom. In addition, the availability of teaching materials that tend to be abstract and offer minimal visualizations makes it difficult for students to understand scientific concepts meaningfully and in ways relevant to everyday life. Based on this, the purpose of this study is to develop an illustrated e-book story based on Balinese local wisdom, "Family Medicinal Plants," to improve the scientific literacy of Grade IV Elementary School Students. This study employs a research-and-development method based on the ADDIE development model. The subjects of this study were 2 media expert lecturers and 2 material expert lecturers. The trial subjects were 3 educators and 10 students. The data collection methods were a questionnaire and an objective test. The data collection instruments used were closed questionnaires and test questions. The analysis techniques used in this study were qualitative and quantitative analysis methods. The assessment results were the average assessment results from media experts, namely 94.8% with the qualification "Very Valid". The assessment results from material experts were 94.8% with the qualification "Very Valid". The teacher's assessment results obtained an average score of 95.83%, and the students' 92.92%, thus qualifying as very practical. The effectiveness test results showed a significant difference in students' scientific literacy before and after using the illustrated story e-book media. It was concluded that the illustrated story e-book based on Balinese local wisdom, "Family Medicinal Plants," is suitable for learning.